Eksplorasi pariwisata di lembah harau "keindahan alam dan pengelolaan berkelanjutan - Silvia Yetti; Yunia Wardi; Retnaningtyas Susanti (JRTI (Jurnal Riset Tindakan Indonesia), 2024)
The Harau Valley area in its journey continues to experience development, concerned with the policies taken by relevant stakeholders. related stakeholders. Previous research shows that the Harau Valley Region is at the Stagnation stage. Furthermore, based on the author's analysis which the life cycle of natural attractions and Sarosah Village as an artificial attraction, shows that the tourism life cycle of the Harau Valley Area artificial attractions, shows that the tourism life cycle of the Harau Valley Region is at the Harau Valley Region is in the rejuvenation stage. The construction of artificial tourist attractions as a rejuvenation effort in developing tourism products in a more attractive direction. more interesting. It is necessary to review the policies that have been set by stakeholders related to the development of the Harau Valley Region. Relevant stakeholders need to hold discussions related to the role of Sarosah Village, which shifts the life cycle  of the Harau Valley Area. which shifted the life cycle of the Harau Valley Area to the rejuvenation stage